Commerce of Edible Insects in the State of Morelos, Mexico. Issue 5 (16th October 2020) - Pino Moreno, José Manuel; Reyes-Prado, Humberto
Abstract: The present study deals with the taxonomical analysis of the edible insects commercialized in the state of Morelos, Mexico. We have recorded two species under the order Orthoptera and four species under Hemiptera–Heteroptera. Our work revealed that grasshoppers and small hemipterans known as 'jumiles' are the two main insects sold in the markets of the state of Morelos. We also discuss insects' prices and their economic importance for the livelihood improvement of the local people connected to the edible insect trade.